This is what a website states:

Before graphing a quadratic function we rearrange the equation, from this:

$f(x) = ax^2 + bx + c$

To this:

$f(x) = a(x-h)^2 + k$


$h = -b/2a$
$k = f( h )$

In other words, calculate h$ (=-b/2a)$, then find $k$ by calculating the whole equation for $x=h$

The website states the following reason for doing this:

Well, the wonderful thing about this new form is that $h$ and $k$ show us the very lowest (or very highest) point, called the vertex:

And also the curve is symmetrical (mirror image) about the axis that passes through $x=h$, making it easy to graph

Image showing the vertex of a quadratic function

I want to know that how is $h$ the x - coordinate and $k$ the y - coordinate of the vertex?


The square of any real number is always at least zero, and equals zero only when that number is itself zero. So $(x-h)^2$ is always at least zero, and is equal to zero only when $x-h=0$; that happens only when $x=h$.

Since $(x-h)^2$ is always at least zero, we see that any positive multiple of it is also always at least zero. So, if we are told that $a>0$, we can say with certainty that $a(x-h)^2$ is always at least zero and is equal to zero only when $x=h$.

Finally, we see that $a(x-h)^2 +k$ is always at least $k$ and is equal to $k$ only when $x=h$. That's because we are adding to $k$ a number that is always at least zero (so, the sum can't be any less than $k$).

Clearly $(h,k)$ is a point on the graph of the function $f(x) = a(x-h)^2+k$. Any other point $(x,y)$ on the graph has an $x$-coordinate that is not $h$, so the $y$-coordinate must be greater than $k$. This means that if we move left or right from $(h,k)$, staying on the graph, we can only move up.


(The case $a<0$ is handled similarly -- try it yourself! What happens if $a=0$?)

Addendum: How to find $h$ and $k$

This is just completing the square to rewrite the original expression. Start with:

$$f(x) = ax^2 + bx + c$$

Now suppose there is and $h$ and a $k$ so that this is the same as

$$f(x) = a(x-h)^2 + k$$

Let's write this out in full : $$a(x-h)^2 + k=a(x^2-2hx + h^2) + k = ax^2-2ahx + ah^2+k$$ Now if these are to be the same function for all $x$, then $$ax^2 + bx + c = ax^2-2ahx + ah^2+k$$ Move everything to one side (note the $ax^2$ terms add out): $$(\underbrace{b+2ah}_{\textrm{constant}})x + (\underbrace{c-ah^2-k}_{\textrm{constant}})=0$$

This has to be true for all $x$. But this is just a linear function of $x$, and the only linear function which is zero for all $x$ is the linear function whose coefficients are all zero! This means we can write $$\begin{cases}b+2ah = 0\\c-ah^2-k = 0\end{cases}$$ So solve the first equation for $h$ to get $$\boxed{h=-\tfrac b{2a}}$$ Now you could plug this into the second equation and solve for $k$, but it's probably easier to note that, since we assumed $$f(x) = a(x-h)^2+k$$ then just putting $x=h$ into this we get $$\boxed{f(h)} = a(h-h)^2+k=a\cdot 0^2 + k = \boxed{k}$$ In other words, get $k$ by using the fact that $$\boxed{k=f(h)}$$ (and we know $h$ at this point).

  • $\begingroup$ I got your point that h and k would be coordinates of vertex. But I still didn't understood how we reached the conclusion that h = -b/2a and k = f(h). $\endgroup$ – Parth Apr 21 '16 at 17:11
  • $\begingroup$ Okay, I added a section in my answer to show how you know this. $\endgroup$ – MPW Apr 21 '16 at 20:25
  • 1
    $\begingroup$ How is b - 2ah = 0? Shouldn't it be b + 2ah? $\endgroup$ – Parth Apr 22 '16 at 0:49
  • $\begingroup$ @unknownCoder: Yes, typo. Will fix. Thanks for the catch, +1. $\endgroup$ – MPW Apr 22 '16 at 12:48
  • $\begingroup$ What is the need of including an a in a(x - h)^2 + k? $\endgroup$ – Parth Apr 22 '16 at 15:13

The quantity $(x-h)^2$ is always non negative, and the smallest value it can attain is zero when $x=h$. Now we have two cases:

1) $a>0$: in this case the quantity $a(x-h)^2$ is always non negative and has zero as its smallest value when $x=h$.

2) $a<0$: in this case the quantity $a(x-h)^2$ is always non positive and has zero as its largest value when $x=h$.

In both cases $x=h$ represents a global minimum or maximum of the function; this property doesn't change if you consider the "shifted" quantity $a(x-h)^2+k$, because adding a constant to a function does not change the position of its maxima or minima.

So the x-coordinate of the vertex is at $x=h$.


(1) All graphs of quadratic functions are symmetric about some vertical axis. $y = f(x) = ax^2 + bx + c $ (where we assume that $a > 0$ for simplicity) is of no exception.

(2) The vertex $V(h, k)$ will lie on that axis.

(3) Let us assume that $f(x) = 0$ has roots $\alpha$ and $\beta$. Then, the graph of y = f(x) will cut the x-axis at $A( \alpha, 0)$ and $B( \beta, 0)$. The point $( \dfrac {\alpha + \beta}{2}, 0)$ is midway between A and B. Then, the vertical axis (of symmetry) has the equation $L : x = \dfrac {\alpha + \beta}{2}$.

(4) Recall that $\alpha + \beta =$ the sum of roots $= \dfrac {–b}{a}$. Therefore, equation of L is then $L : x = \dfrac {–b}{2a}$.

(5) According to (2), $V = (h, k) = (\dfrac {–b}{2a}, k)$; where k is given by $f(\dfrac {–b}{2a})$ or $f(h)$ because $V$ is a point on the curve of $y = f(x)$.

In the case that $f(x) = 0$ has no real roots, (ie. the graph of $y = f(x)$ does not cut the x-axis), we can translate the x-axis upward certain suitable units such that the new X-axis will cut $y = f(x)$. The above argument still applies.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.